Robot & Frank [videorecording (DVD)] - Schreier, Jake; Langella, Frank; Sarandon, Susan, 1946-; Marsden, James, 1973-; Tyler, Liv (Sony Pictures Home Entertainment, 2013)
Frank is an aging ex-jewel thief, and his two grown children are worried that he can no longer care for himself. In deciding what to do with Frank, the most likely option appears to be putting him in a nursing home. But Frank's son comes up with another option: buy Frank a walking, talking robot programmed to look after him and improve his physical and mental health. Frank resists the robot at first, but he warms to it after realizing that it could be the perfect heist companion.